Antimicrobial Resistance in New Zealand-A One Health Perspective - Isabelle Pattis; Louise Weaver; Sara Burgess; James E. Ussher; Kristin Dyet (MDPI AG, 2022)
Antimicrobial resistance (AMR) is an increasing global threat that affects human, animal and, often less acknowledged, environmental health. This complex issue requires a multisectoral One Health approach to address the interconnectedness of humans, animals and the natural environment. The prevalence of AMR in these reservoirs varies widely among countries and thus often requires a country-specific approach. In New Zealand (NZ), AMR and antimicrobial usage in humans are relatively well-monitored and -understood, with high human use of antimicrobials and the frequency of resistant pathogens increasing in hospitals and the community. In contrast, on average, NZ is a low user of antimicrobials in animal husbandry systems with low rates of AMR in food-producing animals. AMR in New Zealand's environment is little understood, and the role of the natural environment in AMR transmission is unclear. Here, we aimed to provide a summary of the current knowledge on AMR in NZ, addressing all three components of the One Health triad with a particular focus on environmental AMR. We aimed to identify knowledge gaps to help develop research strategies, especially towards mitigating AMR in the environment, the often-neglected part of the One Health triad.